Ewing sarcoma gene Ews regulates hematopoietic stem cell senescence - Cho, Joonseok (American Society of Hematology, 2011)
The longevity of organisms is maintained by stem cells. If an organism loses the ability to maintain a balance between quiescence and differentiation in the stem/progenitor cell compartment due to aging and/or stress, this may result in death or age-associated diseases, including cancer. Ewing sarcoma is the most lethal bone tumor in young patients and arises from primitive stem cells. Here, we demonstrated that endogenous Ewing sarcoma gene (Ews) is indispensable for stem cell quiescence, and that the ablation of Ews promotes the early onset of senescence in hematopoietic stem progenitor cells. The phenotypic and functional changes in Ews-deficient stem cells were accompanied by an increase in senescence-associated β-galactosidase staining and a marked induction of p16(INK4a) compared with wild-type counterparts. With its relevance to cancer and possibly aging, EWS is likely to play a significant role in maintaining the functional capacity of stem cells and may provide further insight into the complexity of Ewing sarcoma in the context of stem cells.